Continuity of Care oleh Mahasiswa Kebidanan meningkatkan Efikasi Diri dan Ekspektasi Ibu - Wahyuni, Sri; Istikhomah, Henik; Susilowati, Dewi; Puji Wahyuningsih, Heni (LPPM Universitas Prima Nusantara Bukittinggi, 2026)
Background: Despite the documented benefits of continuity of care for both pregnant women and midwifery students, research on the self-efficacy and expectations of mothers who receive continuity of care from midwifery students remains limited. Objectives: Exploring the self-efficacy and expectations of mothers who receive continuity of care provided by midwifery students. Methods: This study employed a descriptive-analytic design with a cross-sectional approach. A total of 80 mothers who received continuity of care from midwifery students between June and August 2023 participated in the study and provided written informed consent. Data were collected using a self-efficacy and an expectations questionnaire. Participants also completed a demographic characteristics form. The data were analyzed and presented in the form of frequency distributions. Results: The mean age of participants was 30.40±7.39 years. Most participants had a secondary education (50%), unemployed (57.5%), primigravida (52.5%). Self-efficacy was assessed in three aspects: perceived difficulty level (good in 77%), strength of belief (good in 73%), and scope of knowledge (good in 76%). Most mothers reported experiences that met their expectations during pregnancy (90%), labor (83.8%) and the postpartum and breastfeeding period (88.8%) while receiving continuity of care from midwifery students. Conclusion: The CoC model implemented by midwifery students is effective in enhancing pregnant women’s self-efficacy and satisfaction throughout the antenatal, intrapartum, and postnatal periods. It is essential for midwifery students to establish effective and trusting relationships with women to ensure the successful implementation of continuity of care.